2020
DOI: 10.1103/physrevmaterials.4.083403
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate magnet iron monophosphide FeP: Crystal growth and characterization

Abstract: We report an optimized chemical vapor transport method, which allows growing FeP single crystals up to 500 mg in mass and 80 mm 3 in volume. The high quality of the crystals obtained by this method was confirmed by means of EDX, high-resolution TEM, low-temperature single crystal XRD and neutron diffraction experiments. We investigated the transport and magnetic properties of the single crystals and calculated the electronic band structure of FeP. We show both theoretically and experimentally, that the ground … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(55 reference statements)
4
9
0
Order By: Relevance
“…We assumed a paramagnetic configuration because of the small magnetic moment [3], which is a consequence of the octahedral crystal field that inverts the 4s and 3d energetic levels and changes the Fe configuration from commonly observed d 6 to d 8 . The band structure is similar to that recently reported [33], though our Fermi level appears to be at a slightly lower energy, which somewhat alters the appearance of the Fermi surface. The nonsymmorphic symmetry of the MnP-type structure implies the presence of several linear bands and semi-Dirac points.…”
Section: Quantum Oscillations and Electronic Structuresupporting
confidence: 87%
“…We assumed a paramagnetic configuration because of the small magnetic moment [3], which is a consequence of the octahedral crystal field that inverts the 4s and 3d energetic levels and changes the Fe configuration from commonly observed d 6 to d 8 . The band structure is similar to that recently reported [33], though our Fermi level appears to be at a slightly lower energy, which somewhat alters the appearance of the Fermi surface. The nonsymmorphic symmetry of the MnP-type structure implies the presence of several linear bands and semi-Dirac points.…”
Section: Quantum Oscillations and Electronic Structuresupporting
confidence: 87%
“…High quality single crystals of FeP up to 500 mg in mass and 80 mm 3 in volume were grown by chemical vapor transport with iodine as a transport agent. The quality of the crystals were confirmed by means of EDX, XRD, magnetic, transport, high resolution TEM and single-crystal neutron diffraction experiments [36]. The temperature dependence of the resistivity shows the typical metallic behavior with a residual resistivity ratio RRR = 566.…”
Section: A Experimental Detailsmentioning
confidence: 85%
“…The temperature dependence of the resistivity shows the typical metallic behavior with a residual resistivity ratio RRR = 566. Below the the Néel temperature T N = 119.3 K, analysis of the neutron diffraction data yields an incommensurate magnetic structure with the propagation vector Q = (0, 0, ±δ), where δ ≈ 0.2 [1,36]. For neutron spectroscopy measurements, we used a single crystal with a mass of ∼0.5 g.…”
Section: A Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 3(a)-3(c) summarize the main features of the magnetic spectra of FeP at a temperature of 7.5 K. The previous neutron diffraction measurements on single crystals [20,36], as well as our powder neutron diffraction data shown in the Supplemental Materials [37] showed that the helical magnetic structure yields pairs of strong magnetic satellites at the momenta (1 1 0) ±k and (1 0 1) ±k, where k = (0 0 0.2) r.l.u. The elastic (E = 0) slice through the dataset in the vicinity of the momentum transfer Q = (1 1 0), which is a forbidden Bragg reflection for the nuclear structure, is shown in Fig.…”
Section: Tof Spectroscopy a Observed Spectramentioning
confidence: 92%